2019
DOI: 10.3389/fchem.2019.00108
|View full text |Cite
|
Sign up to set email alerts
|

Extending Catalyst Life in Glycerol-to-Acrolein Conversion Using Non-thermal Plasma

Abstract: Booming biodiesel production worldwide demands valorization of its byproduct of glycerol. Acrolein, an important intermediate chemical, can be produced by gas-phase glycerol dehydration catalyzed by solid acids. Because catalysts that lead to high acrolein selectivity usually deactivate rapidly due to the formation of coke that blocks the active sites on their surface, one major challenge of this method is how to extend the service life of the catalyst. Silica-supported silicotungstic acid (HSiW-Si) is a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In our previous study using a regular catalyst, we found no difference in XRD patterns between the fresh catalyst and spent catalyst in that the deposited coke was amorphous and would not change the crystalline structure of the catalyst on which it was deposited. Importantly, the coke formation significantly decreased the glycerol conversion with only minor impact on the selectivity to acrolein; with periodic regeneration using oxygen-containing NTP at low temperatures, the glycerol conversion could be effectively restored [25].…”
Section: Catalyst Performance In Glycerol Dehydrationmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study using a regular catalyst, we found no difference in XRD patterns between the fresh catalyst and spent catalyst in that the deposited coke was amorphous and would not change the crystalline structure of the catalyst on which it was deposited. Importantly, the coke formation significantly decreased the glycerol conversion with only minor impact on the selectivity to acrolein; with periodic regeneration using oxygen-containing NTP at low temperatures, the glycerol conversion could be effectively restored [25].…”
Section: Catalyst Performance In Glycerol Dehydrationmentioning
confidence: 99%
“…The supported HSiW catalysts on Al (denoted as HSiW-Al) and Si (denoted as HSiW-Si) fabricated with different methods were tested and compared in glycerol dehydration reactions carried out in a down-flow packed-bed reactor at 275 • C and atmospheric pressure. Detailed description of the experiment and evaluation of catalyst performance can be found in our previous publication [25]. Briefly, the reactor was made of a quartz tube (length 300 mm, ID 19.35 mm, OD 25.3 mm), which was heated by a heating tape evenly wrapped around the outer wall of the quartz tube.…”
Section: Glycerol Dehydration To Acroleinmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the value-added chemicals that can be derived from glycerol, acrylic acid produced via the intermediate of glycerol dehydration to acrolein received much attention because this appears to be one of the most promising ways to valorize glycerol [4,5]. There have been extensive efforts in recent years to improve glycerol dehydration to acrolein, including glycerol conversion in sub-and supercritical water [6][7][8], as well as selective gas-phase conversions [9][10][11][12][13]. Although these different processes gave adequate glycerol conversion rates and selectivity to acrolein, a continuous process catalyzed by solid acids is desirable for industrial application.…”
Section: Introductionmentioning
confidence: 99%